Teacher and Student Directive Speech Acts in Learning Writing Indonesian (Pragmatic Studies) - Heni Arifa; Sumarti Sumarti; Mulyanto Widodo (Budapest International Research and Critics University, 2022)
This study aims to explain and describe the directive speech acts contained in conversations between teachers and students in learning to write Indonesian. The type of research used is descriptive qualitative. The data in this study are the utterances or conversations of teachers and students carried out in the learning process. The results show that teachers and students use directive speech acts with declarative, interrogative and imperative modes in conversation in the process of learning to write Indonesian with a communicative function contained are ordering, requesting, suggesting, advising, prohibiting, motivating and asking. Thus, conversations in learning to write Indonesian between teachers and students use direct and indirect speech acts.